Radiation, soil water content, and temperature effects on carbon cycling in an alpine swamp meadow of the northeastern Qinghai–Tibetan Plateau - Wei, Junqi; Li, Xiaoyan; Liu, Lei; Christensen, Torben Røjle; Jiang, Zhiyun; Ma, Yujun; Wu, Xiuchen; Yao, Hongyun; López-Blanco, Efrén (Biogeosciences, 2022)
Predicted intensified climate warming will likely alter the ecosystem net carbon (C) uptake of the Qinghai–Tibetan Plateau (QTP). Variations in C sink–source responses to climate warming have been linked to water availability; however, the mechanisms by which net C uptake responds to soil water content in saturated swamp meadow ecosystems remain unclear. To explore how soil moisture and other environmental drivers modulate net C uptake in the QTP, field measurements were conducted using the eddy covariance technique in 2014, 2015, 2017, and 2018. The alpine swamp meadow presented in this study was a persistent and strong C sink of CO 2 ( −168.0 ± 62.5 g C m −2 yr −1 , average ± standard deviation) across the entire 4-year study period. A random forest machine-learning analysis suggested that the diurnal and seasonal variations of net ecosystem exchange (NEE) and gross primary productivity (GPP) were regulated by temperature and net radiation. Ecosystem respiration (Re), however, was found mainly regulated by the variability of soil water content (SWC) at different temporal aggregations, followed by temperature, the second contributing driver. We further explored how Re is controlled by nearly saturated soil moisture and temperature comparing two different periods featuring almost identical temperatures and significant differences on SWC and vice versa. Our data suggest that, despite the relatively abundant water supply, periods with a substantial decrease in SWC or increase in temperature produced higher Re and therefore weakened the C sink strength. Our results reveal that nearly saturated soil conditions during the growing seasons can help maintain lower ecosystem respiration rates and thus enhance the overall C sequestration capacity in this alpine swamp meadow. We argue that soil respiration and subsequent ecosystem C sink magnitude in alpine swamp meadows could likely be affected by future changes in soil hydrological conditions caused by permafrost degradation or accelerated thawing–freezing cycling due to climate warming.